Visual representation of gender in flood coverage of Pakistani print media - Ali, Zarqa S. (Weather and Climate Extremes, 2014)
This paper studies gender representation in the visual coverage of the 2010 floods in Pakistan. The data were collected from flood visuals published in the most circulated mainstream English newspapers in Pakistan, Dawn and The News. This study analyses how gender has been framed in the flood visuals. It is argued that visual representation of gender reinforces the gender stereotypes and cultural norms of Pakistani society. The gender-oriented flood coverage in both newspapers frequently seemed to take a reductionist approach while confining the representation of women to gender, and gender-specific roles. Though the gender-sensitive coverage displayed has been typical, showing women as helpless victims of flood, it has aroused sentiments of sympathy among readers and donors, inspiring them to give immediate moral and material help to the affected people. This agenda set by media might be to exploit the politics of sympathy but it has the effect of endorsing gender stereotypes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cinéma; communication; discipline; environnement; inondations; médias; pakistan; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; stéréotypes de genre; systèmes d'oppressions; thématiques

Idle No More: identité autochtone actuelle, solidarité et justice sociale : Entrevue avec Melissa Mollen Dupuis et Widia Larivière - Gentelet, Karine (Nouvelles pratiques sociales, 2014)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; environnement; féminisme autochtone; militance; pol4105; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; science politique et droit; thématiques

Combattre maintenant les inégalités sexuées, sociales et territoriales dans les quartiers politique de la ville et dans les territoires ruraux fragilisés - Haut Conseil à l'Égalité entre les femmes et les hommes (2014)
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discipline; environnement; europe; france; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; systèmes d'oppressions; thématiques; travail; urbanisme

A question for women's health: Chemicals in feminine hygiene products and personal lubricants - Nicole, Wendee (Environmental Health Perspectives, 2014)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; corps; environnement; perturbateurs endocriniens; produits d'hygiène féminine; produits toxiques; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; états-unis